2023
DOI: 10.1590/s1677-5538.ibju.2023.0021
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic pyeloplasty proficiency during a residency program after adoption of a standardized simulation training program is maintained during the COVID pandemic despite reduced surgery volume

Abstract: Purpose: To evaluate the effect of the standardized laparoscopic simulation training program in pyeloplasty, following its implementation and during the COVID-19 pandemic. Material and Methods: A retrospective chart review was performed at Hospital de Clínicas de Porto Alegre , a tertiary referral center in south Brazil, in which 151 patients underwent laparoscopic pyeloplasty performed by residents between 2006-2021. They were divided into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Dr. Gorgen and collegues form Brazil performed on page 462 ( 4 ) an interesting study about the laparoscopic pyeloplasty learning curve improvement by a standardized simulation training program and concluded that a structured laparoscopic simulation program can improve outcomes of laparoscopic pyeloplasty during the learning curve.…”
mentioning
confidence: 99%
“…Dr. Gorgen and collegues form Brazil performed on page 462 ( 4 ) an interesting study about the laparoscopic pyeloplasty learning curve improvement by a standardized simulation training program and concluded that a structured laparoscopic simulation program can improve outcomes of laparoscopic pyeloplasty during the learning curve.…”
mentioning
confidence: 99%